2018
DOI: 10.1007/s40519-018-0578-y
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of depressive symptoms in obese subjects starting treatment and not seeking treatment for obesity

Abstract: Introduction The psychological profile of obese people deciding to start obesity treatment may be different from those not choosing to seek the therapy. Previous studies have shown a higher incidence of depression in obese than in normal weight people. However, data are lacking concerning the occurrence of depressive symptoms and their severity in obese subjects who do or do not decide to start treatment for obesity. Therefore, the aim of this study was to evaluate the prevalence and severity of depressive sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Our study has shown that patients with obesity starting obesity treatment more often have a high level of body size dissatisfaction than volunteers with obesity not seeking treatment for obesity. This confirms the initial hypothesis of psychological heterogeneity of subjects living with obesity by Fitzgibbon [ 8 ] and is in line with previous findings showing a higher frequency of depression symptoms in people with obesity starting obesity treatment than in volunteers with obesity not seeking treatment for obesity [ 9 ]. It should be noted that adjustment for age and BMI values did not influence obtained results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study has shown that patients with obesity starting obesity treatment more often have a high level of body size dissatisfaction than volunteers with obesity not seeking treatment for obesity. This confirms the initial hypothesis of psychological heterogeneity of subjects living with obesity by Fitzgibbon [ 8 ] and is in line with previous findings showing a higher frequency of depression symptoms in people with obesity starting obesity treatment than in volunteers with obesity not seeking treatment for obesity [ 9 ]. It should be noted that adjustment for age and BMI values did not influence obtained results.…”
Section: Discussionsupporting
confidence: 92%
“…A previously published study revealed that there were more women with moderate and severe depressive symptoms in the group starting treatment than in the group not seeking treatment for obesity (44.7 and 24.4%, respectively). Such a difference was not observed in males [ 9 ]. However, a more detailed characterisation of people willing to take treatment of obesity supervised by physicians and other medical professionals and subsequent interventions toward the improvement of treatment-seeking rate seems to be an important concern of public health.…”
Section: Introductionmentioning
confidence: 93%
“…Somatic and physical items of the BDI, such as distortion of body image, work inhibition, sleep disturbance, fatigability, loss of appetite, somatic preoccupation, loss of libido, and weight loss can overlap with the symptoms of obesity rather than being due to depressive symptomatology 26 , 27 . Previously published studies reported that patients with obesity or patients undergoing bariatric surgery endorsed the somatic-vegetative items more than the cognitive affective items of the BDI 28 , 29 .…”
Section: Methodsmentioning
confidence: 99%